Relationship between workload and symptoms during the ergometric test in patients with interstitial lung disease and healthy individuals (Research, Society and Development, 2022)
Introduction: Interstitial lung diseases (ILD) present similar clinical characteristics such as dyspnea and exercise intolerance. These characteristics are accentuated during physical exertion, although this has not yet been investigated in depth in this population. Aims: To compare the subjective sensation of dyspnea and fatigue by workload during exercise testing (ET) between patients with ILD and healthy subjects. Methods: The individuals performed the CPET on a cycle ergometer with an incremental protocol. At each stage of the test, the sensation of exertion was collected using the Borg scale of dyspnea (D) and fatigue (F). The slopes of the D and F curves by stage in the test were compared using linear regression using the Zar method (F test). Results: 37 patients with ILD and 29 controls were studied. The ILD group had a lower maximum load (60[40-80] vs healthy 120[100-160]; (P